A comparative study of fosfomycin trometamol and nitrofurantoin in acute uncomplicated urinary tract infection - Smita Parate (International Journal of Medical Research and Review, 2016)
Background: Acute urinary tract infection is stressful situation for women. Uncomplicated urinary tract infections are considered to be the most common bacterial infection in women. For treating these uncomplicated UTIs, susceptibility is of critical importance in selecting an appropriate antimicrobial agent.Material and Methods: A case control study carried out in department of obstetrics and gynecology in tertiary care teaching institute in north India. Total 100 female non pregnant patients aged 18 – 65 years with acute uncomplicated UTI were taken in two groups each having 50 cases. The 50 patients of study group were given single 3 gram dose of fosfomycin trometalol orally, while the 50 patients of control group were given 100 mg tab of nitrofurantoin twice daily after food for 7 days, treated on OPD basis, Clinical and microbiological reassessment performed in 7-8 days after the start of treatment and long term follow up at one month from the start of the treatment were done.Results: Mean age of the patients in fosfomycin group was 31.6 years and in nitofurantoin group was 33.8 years. The most frequently isolated microorganism in both the groups were E coli 88% and 86 % respectively based on antibiotic susceptibility of all uropathogens, fosfomycin (91.8%) was the most active antibiotic followed by nitrofurantoin (91.2%) and norfloxacin. Bacterial eradication after 7 days follow up was obtained in 90 % in fosfomycin group as compared to 85% in control group. And long term follow up at one month gave eradication in 81 % in fosfomycin group as compared to 80 % in nitrofurantoin group.Conclusion: This study concludes that fosfomycin trometalol in a single 3-4 gram dose is as effective as 7 day regimen of nitrofurantoin for the treatment of uncomplicated lower urinary tract infection in women. So based on comparable microbiological cure and cost effectiveness and less adverse effects, we conclude that single dose fosfomycin trometalol is a good alternative in the treatment of women with acute uncomplicated UTI.